Literature Review Penerapan Teknologi Informasi dan Metode Pengukuran Pada Audit Kepuasan Pelanggan - Oktaviana Soleman, Charolina Devi; Sudarma, Made; Pramaita, Nyoman (Majalah Ilmiah Teknologi Elektro; Vol 20 No 2 (2021): (Juli-Desember) Majalah Ilmiah Teknologi Elektro, 2021)
Customer loyalty is very important in the sustainability of a business, to maintain customer loyalty, companies are required to understand the level of customer satisfaction and complaints that arise in the service delivery process, manual questionnaires will prevent companies from obtaining customer satisfaction measurement results quickly and accurately. , the faster development of information technology is expected to be able to assist companies in the customer satisfaction audit process, both from the process of distributing questionnaires and processing customer satisfaction measurement data, the results of the literature study show that the application of information technology combined with methods in customer satisfaction audits can help companies in obtaining information related to the results of measuring customer satisfaction quickly and with ease of access, so that stakeholders in the company can take corrective actions to resolve complaints. customer satisfaction and increased performance improvement according to the level of customer satisfaction, from the research results obtained 95% of website-based technology is still widely used in the customer satisfaction audit process and 34% of the CSI method is the method most often applied for measuring customer satisfaction.